X-ray Surface Brightness Profiles of Active Galactic Nuclei in the Extended Groth Strip: Implications for AGN Feedback. (4th January 2016) - Chatterjee, Suchetana; Newman, Jeffrey A.; Jeltema, Tesla; Myers, Adam D.; Aird, James; Coil, Alison L.; Cooper, Michael; Finoguenov, Alexis; Laird, Elise; Montero-Dorta, Antonio; Nandra, Kirpal; Willmer, Christopher; et al.
Abstract: Using data from the All Wavelength Extended Groth Strip International Survey (AEGIS) we statistically detect the extended X-ray emission in the interstellar medium (ISM)/intracluster medium (ICM) in both active and normal galaxies at 0.3 ≤  z  ≤ 1.3. For both active galactic nuclei (AGN) host galaxy and normal galaxy samples that are matched in restframe color, luminosity, and redshift distribution, we tentatively detect excess X-ray emission at scales of 1-10″ at a few σ significance in the surface brightness profiles. The exact significance of this detection is sensitive to the true characterization of Chandra's point-spread function. The observed excess in the surface brightness profiles is suggestive of lower extended emission in AGN hosts compared to normal galaxies. This is qualitatively similar to theoretical predictions of the X-ray surface brightness profile from AGN feedback models, where feedback from AGN is likely to evacuate the gas from the center of the galaxy/cluster. We propose that AGN that are intrinsically underluminous in X-rays, but have equivalent bolometric luminosities to our sources will be the ideal sample to study more robustly the effect of AGN feedback on diffuse ISM/ICM gas.